State identity in Europe today: Some determinants - Raciborski, Jacek; Rafałowski, Wojciech (Journal of Public Governance, 2018)
Objectives: The article is aimed at studying the differentiation of the strength of state identity in selected European countries and attempts to explain the observed tendencies.Research Design & Methods: The empirical part is based upon three waves of the International Social Survey Programme entitled ‘National Identity’.Findings: The results show that state identities in Western European countries are well-developed. Central/Eastern European societies are characterised by lower levels of state identity than Western European ones. We attribute this phenomenon to legacies of the past, especially the to many centuries of economic underdevelopment of the region that was enhanced increased by communism and low levels of social capital in Eastern European societies.Contribution: This study links the state identity of citizens of European countries with their living conditions and past legacies.Article Classification: Research articleKeywords: state identity, national identity, social capital, communist legacy, post-communist countriesJEL classification: H1, H4, P3, P5